Condensation and partial pressure change as a major cause of airflow: Experimental evidence (2017)
The dominant model of atmospheric circulation is based on the notion that hot air rises, creating horizontal winds. A second major driver has been proposed [1] in the biotic pump theory (BPT), by which intense condensation is the prime cause of surface winds from ocean to land. Critics of the BPT argue that air movement resulting from condensation is isotropic [2]. This paper explores the physics of water condensation under mild atmospheric conditions, within a purpose-designed square-section 4.8m-tall closed-system structure. The data show a highly significant correlation (R2 0.96, p value 0.001) between observed airflows and partial pressure changes from condensation. The assumption that condensation of water vapour is always isotropic is therefore incorrect. This does not prove that condensation and cloud-formation cause atmospheric surface winds, but the implications are that the correlation found in the experiments needs to be considered for the atmosphere at large.